Pengaruh Metode Latihan Interval Ekstensif Terhadap Kemampuan VO2 Maks Siswa Sekolah Sepakbola Puncak Andalas Kerinci - Elka Pianda; Didin Tohidin (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2019)
ABSTRACT The problem in this study is the still low ability of VO2 Max U-15 football school students at Andalas Peak Kerinci. The study aims to determine: Effect of Extensive Interval Training Methods on the ability of VO2 Max students of U-15 Football School in Andalas Peak Kerinci. The type of research is Quasi Experiment (Quasy Experiment). The population in this study were students of the Andalas Kerinci Peak football school, totaling 57 people with U-10, U-12, U-15 and U-15 groups totaling 13 people as Samples. Samples are taken throughtechniques Purposive Sampling. Instrument Research on the ability of VO2 Max, which is a series of tests applied are: Bleeps Test. Data analysis for testing the research hypothesis using the t-test with a significance level α = 0.05. Based on the results of the research carried out it can be concluded that: There is a significant effect oftraining methods on extensive intervalthe ability of VO2 Max of the Andalas Peak U-15 Soccer school students in Kerinci, with tcount > ttable (6.02> 1.78), from the mean pre test (31.77) becomes the mean post test (36.59). ABSTRAK Masalah dalam penelitian ini adalah masih rendahnya Kemampuan VO2 Maks siswa sekolah sepakbola U-15 Puncak Andalas Kerinci. penelitian bertujuan untuk mengetahui : Pengaruh Metode Latihan Interval Ekstensif Terhadap kemampuan VO2 Maks siswa sekolah Sepakbola U-15 Puncak Andalas Kerinci. Jenis penelitian adalah Eksperimen Semu (Quasy Eksperimen). Populasi dalam penelitian ini adalah siswa sekolah sepakbola Puncak Andalas Kerinci yang berjumlah 57 orang dengan kelompok U-10, U-12, U-15 dan kelompok U-15 berjumlah 13 orang sebagai Sampel. Sampel diambil melalui teknik Purposive Sampling. Instrument Penelitian kemampuan VO2 Maks yaitu rangkaian tes yang diberlakukan adalah: Bleeps Test. Analisis data untuk pengujian hipotesis penelitian menggunakan uji-t dengan taraf signifikan α = 0,05. Berdasarkan hasil penenlitian yang telah dilaksanakan dapat disimpulkan bahwa : Terdapat pengaruh yang signifikan Metode latihan interval ekstensif Terhadap Kemampuan VO2 Max siswa sekolah Sepakbola U-15 Puncak Andalas Kerinci, dengan thitung > ttabel (6.02 > 1.78), dari mean pre-test (31.77) menjadi mean post test (36.59).